Formas de socialização do conhecimento por cientistas: as redes sociais em perspectiva - Gomes, Diego Diniz Ferreira (2021)
When considering the context of scientific dissemination practices in the blogs and Instagram profiles of scientists in the field of Chemistry Teaching, the general objective of this research was to analyze the relationships established between scientific practice and its socialization by scientists, within the scope of social networks, seeking the relationships established in a new model of scientific dissemination. The netnographic method was used as a methodological path for this investigation, which has its origins in ethnography and as a basis the study of behavior in digital environments. We have as a guiding question for the research: how do scientists in the Chemistry Teaching area position themselves in relation to scientific dissemination on their blogs and Instagram and how the interaction processes established in these networks contribute to the circulation of scientific knowledge? To answer this question, theoretical discussions were held about cyberspaces and the relationships that are produced in them and, finally, we sought to discuss issues related to scientific dissemination and the production of fake news on social networks and how these have an impact on society. Four pages of blogs in the area of Chemistry Teaching and five Instagram profiles were selected that have a direct relationship with the pages of the blogs. Through the immersion carried out in these networks and in the pages of the blogs, two categories of analysis emerged: the relationship between the pages of the blogs and scientific dissemination, and the interaction established with Internet users on Instagram. As a result of these analyses, it was shown at first that the pages of the blogs fulfill the function of the content characteristic of the practices of scientific dissemination, however, there was a disuse by the subjects who access these pages. Regarding Instagram profiles, we can show that they carry out scientific dissemination, however, engagement on these pages is still low and this may be a result of the Instagram algorithm in the delivery of content. Finally, we conclude that making scientific dissemination in social networks can contribute to the circulation of scientific knowledge, however, it is necessary to broaden the discussions on this theme to understand in a more profound way the real reach of these pages and profiles with the public curious about science.